Niat Ganda untuk Satu Amal - Zulkarnaini Zulkarnaini (Universitas Islam Negeri Imam Bonjol Padang, 2013)
A charitable or religious activities can be positive, it may not. A worship, such as prayer, worship shall be doomed, could also be worth worship on alternate days. Furthermore, a worship can be called with a specific name, can also be given other names. Likewise, a charity may contain one kind of worship, can also be. All of it is determined by the relevant intention.